How to Use Beneficial Nematodes against Pest Mole Crickets in Home Lawns - Jennifer L. Gillett-Kaufman; Norman C. Leppla; J. Howard Frank (EDIS)
IPM-144, a 2-page illustrated fact sheet by J. L. Gillett, N. C. Leppla and J. H. Frank, provides homeowners with the information they need to purchase and use biological control nematodes to manage pest mole crickets in their lawns. Published by the UF Department of Entomology and Nematology, September 2006.